2022
DOI: 10.3390/ijerph19074275
|View full text |Cite
|
Sign up to set email alerts
|

Health Equity Implications of the COVID-19 Lockdown and Visitation Strategies in Long-Term Care Homes in Ontario: A Mixed Method Study

Abstract: The COVID-19 pandemic has negatively impacted the lives and well-being of long-term care home residents. This mixed-method study examined the health equity implications of the COVID-19 lockdown and visitation strategies in long-term care homes in Ontario. We recruited long-term care home residents, their family members and designated caregivers, as well as healthcare workers from 235 homes in Ontario, Canada. We used online surveys and virtual interviews to assess the priority, feasibility, and acceptability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…However, LTC residents face challenges during video calls with families via tablets/computers ( Hardy et al., 2022 ; Ickert et al., 2020 ). Many LTC homes have poor Internet connections and limited devices, which restricts the opportunity for virtual visits ( Chu et al, 2022 ; Saad et al, 2022 ). Physical, cognitive, and sensory impairments of LTC residents also impede their independence in using technologies ( Chu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, LTC residents face challenges during video calls with families via tablets/computers ( Hardy et al., 2022 ; Ickert et al., 2020 ). Many LTC homes have poor Internet connections and limited devices, which restricts the opportunity for virtual visits ( Chu et al, 2022 ; Saad et al, 2022 ). Physical, cognitive, and sensory impairments of LTC residents also impede their independence in using technologies ( Chu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study found that technological and virtual innovations were effective strategies to promote a stronger family presence in LTC 32 . For Saad et al, 31 86.6% of participants perceived remote visits as a viable strategy. Digital technology allowed residents to participate in family events, bond with geographically distant relatives, and expand their cultural and entertainment opportunities, which were previously hindered.…”
Section: Discussionmentioning
confidence: 96%
“…Despite health professionals with fear of contamination, the return of in-person visits from family and volunteers improved the well-being of older adults living in LTCF. 29 , 30 Saad et al 31 surveyed LTCF residents, family members, caregivers, and clinical and management staff about the implications for health inequalities of suspending visits in Canada (Ontario). They indicated that suspending visits was considered unfair and a violation of the rights of residents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations